The Influence of Example non Example Learning Models for the Result on Theme 3 Subtheme 2 in Grade III SD Negeri 097805 Rambung Merah - Wendaria Haloho; Muktar B. Panjaitan; Selamat Triadil Saragih (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of the model Example non Example on student learning outcomes Theme 3 Subtheme 2 in k class III SD Negeri 097805 Rambung Merah , the method in this research is a quantitative experimental type method whose research design is pre-experimental type one group pretest-posttest. Which will be carried out on October 15 to October 25 2023. 2023, the population in this study is all students of class I II SDN 097805 Rambung Merah with a total of 2 2 students used, namely purposing sampling with two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable (y) in the form of a model Example non Example. Data collection techniques are test techniques with validity tests, reliability tests, difficulty level tests, and differentiating power tests. The results of hypothesis testing using the normality test, homogeneity test, and T-test with the help of the SPSS version 21 program, obtained t count = 11.287 with a significant level (2-tailed) 0.000, significant probability <0.05, t count > t table = 11.287>2.086 then H 0 is rejected and Ha is accepted. This explanation shows that there is an influence of the Example Non Example learning model on student learning outcomes in theme 3 class II of SD N 097805 Rambung Merah.